The social marketing strategies implemented by SPEK-HAM Surakarta for violence prevention in 2024 (BIS Humanities and Social Science, 2026)
Social marketing in violence prevention serves as a strategic approach to raising public awareness, changing behavior, and building a safe and violence-free social environment. This study aims to analyze the implementation of social marketing strategies carried out by SPEK-HAM Surakarta in violence prevention efforts throughout 2024, based on the social marketing theory proposed by Kotler and Andreasen, using an analytical framework of stages and the 4P+3P marketing mix. This study employs a descriptive qualitative method through a case study approach, with data collected through in-depth interviews and documentation. The results show that SPEK-HAM’s social marketing strategies are implemented through digital media–based education and direct activities such as socialization and training. However, the implementation in digital media is not yet optimal due to the lack of clear positioning in developing educational messages and continued dependence on other organizations’ campaigns. In addition, limited human resources also pose a challenge to information dissemination. Therefore, it is necessary to strengthen the social marketing strategy through consistent positioning and varied digital content formats to enhance the effectiveness of educational messages.